2014
DOI: 10.1159/000363002
|View full text |Cite
|
Sign up to set email alerts
|

Association of the 3'UTR FOXO3a Polymorphism rs4946936 with an Increased Risk of Childhood Acute Lymphoblastic Leukemia in a Chinese Population

Abstract: Background/Aims: FOXO3a is an essential tumor suppressor that regulates the mechanisms of tumorigenesis and leukemogenesis. FOXO3a polymorphisms have not been reported previously associated with an increased risk for childhood acute lymphoblastic leukemia (ALL). In this study, the rs4946936 polymorphism located in the 3'UTR of FOXO3a was selected to evaluate its relationship with a risk for ALL in Chinese children. Methods: Questionnaires, SNaPshot genotyping, real-time PCR, cell transfection and dual lucifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 15 publications
0
41
0
Order By: Relevance
“…Multiple GWAS identified a series of risk loci such as ARID5B, IKZF1, GATA3, CDKN2A, and BMI1-PIP4K2A [6,7,8,9], which have not been consistently identified across these GWAS but validated by meta-analyses. Our previous studies have demonstrated that polymorphisms in the PI3K-AKT pathway are associated with risk for childhood ALL [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Multiple GWAS identified a series of risk loci such as ARID5B, IKZF1, GATA3, CDKN2A, and BMI1-PIP4K2A [6,7,8,9], which have not been consistently identified across these GWAS but validated by meta-analyses. Our previous studies have demonstrated that polymorphisms in the PI3K-AKT pathway are associated with risk for childhood ALL [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence demonstrating that SNPs localized at miRNA binding sites (miRSNPs) could affect the binding of miRNAs to the target genes and in turn result in reduction or increase in translation of the target mRNA and altered susceptibility to cancer [28, 32]. For example, previous studies showed that the rs2910164 polymorphism harboring the sequence for miR-146a could influence susceptibility to gastric cancer in a Chinese population, while rs4143815 and rs4819388 SNPs in the 3'-UTR of B7-H1 and B7-H2 genes, respectively, associated with development of gastric cancer [33-35].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, genomic DNA samples of 10 ng each were amplified using PCR in a total volume of 5 µL containing TaqMan Universal Master Mix, 80x SNP Genotyping AssayMix, DNase-free water and 10-ng DNA. The PCR conditions were 50 °C for 2 min and then 95 °C for 10 min, followed by 40 cycles of 95 °C for 15 s and 60 °C for 1 min in a 384-well ABI 7900HT Real Time PCR System as described previously [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Currently, miRNA has been documented as function factor involved in the SNP associated post-transcriptional regulation [4, 5]. The binding of certain miRNA could be influenced in different genotypes causing the different expression of mRNA level with [6, 7].…”
Section: Introductionmentioning
confidence: 99%